2016
DOI: 10.1371/journal.pone.0166321
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Functional and Phylogenetic Analysis of Sperm Lysozyme-Like Proteins

Abstract: Sperm lysozyme-like proteins belonging to c-type lysozyme family evolved in multiple forms. Lysozyme-like proteins, viz., LYZL2, LYZL3 or SLLP1, LYZL4, LYZL5 and LYZL6 are expressed in the testis of mammals. Not all members of LYZL family have been uniformly and unambiguously identified in the genome and proteome of mammals. Some studies suggested a role of SLLP1 and LYZL4 in fertilization; however, the function of other LYZL proteins is unknown. We identified all known forms of LYZL proteins in buffalo sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Lysozyme-C family is named after hen egg white lysozyme, its prototypical member. This family includes lysozymes, lysozyme-like proteins and alpha-lactalbumins (2629). Some lysozymes bind calcium [Ca(+)-Lys] whereas others do not [Ca(-)-Lys].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysozyme-C family is named after hen egg white lysozyme, its prototypical member. This family includes lysozymes, lysozyme-like proteins and alpha-lactalbumins (2629). Some lysozymes bind calcium [Ca(+)-Lys] whereas others do not [Ca(-)-Lys].…”
Section: Resultsmentioning
confidence: 99%
“…alpha-Lactalbumins have lost catalytic activity but have acquired a new function wherein, as part of the lactose synthase complex, they modify the acceptor substrate specificity of beta-1,4-galactosyltransferase (30). Phylogenetic analyses have indicated that alpha-lactalbumins and lysozymes diverged from a common ancestor, a calcium binding protein (28, 29) (Figure S1). The vestiges of divergence are evident in lysozymes that retain calcium-binding ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the c‐type LYZs are primarily expressed in the testis 13,14,27–30 . Among them, LYZL4, 14 LYZL6, 13 and SPACA3, also named SLLP1, 12 are found to be acrosomal proteins and are implicated in sperm–oocyte fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Tears help physically remove material from the eyes and contain lysozymes-hydrolytic enzymes that cleave glyosidic bonds in Nacetylmuramic acid and N-acetylglucosamine-which break down peptidoglycan in the cell walls of bacteria. 7 If a foreign molecule is able to make it past these initial barriers, then the immune system must respond accordingly.…”
Section: Immune System Componentsmentioning
confidence: 99%